MOVEMENT OF THE CAR ON THE DESCENT OF THE HILL (World Bulletin of Management and Law, 2022)
The article clarified the cause of the moment of rolling friction due to the impact of the rail on the wheel (or reaction in-ideal constant on the wheel) and identified a condition of the lack of wheel rolling along the rail. In her final analytical formulas and examples of calculations proved that in the areas of deceleration at the stations the brake position hump happen to slip of the wheels of the wheel pairs of the car. For this reason is erroneous determination of sliding speed of the car at the stations the brake position according to the formula of free fall of bodies, taking into account the inertia of the rotating parts.